A influência da rede de relacionamentos no processo de internacionalização da Citri Agroindustrial - Correia, Renato Valença (2016)
This research aimed to understand how the network of relationships influenced the process of internationalization of Citri Agroindustrial, however, to achieve this goal, the following specific objectives were set: a) describe the network of relationships of Citri Agroindustrial; b) describe the process of internationalization of Citri Agroindustrial and c) describe how the network of relationships influenced the internationalization of Citri Agroindustrial. Therefore, a qualitative research of descriptive type was developed using the methodological strategy of case study. The primary data collection occurred through six interviewsand five interviewed people, with two interview scripts aplied, one for the members of Agroindustrial Citri and another for the respondents from COACIPAR, as well as non-participant observation. Secondary data were collected in magazines specialized in foreign trade,company documents and the trade association of the city of Paranavaí. The case study analysis made the company realize that the Agroindustrial Citri used, and outside input mode of direct export, carried out by an SalesAgent, and it can be categorized as a born global, yet even with this feature, the company also has gradual internationalization features proposed by the Uppsala School. In this analysis we realized the relevance and centrality of the respondent 1 relationships with all other network actors of Agroindustrial Citri network, such as with members of the company, SalesAgent, competitors (Cutrale, Louis Dreyfus and Centrosul), port owners, international certification directors of Fair Trade (FLO-CERT) and COACIPAR.